Substitution behaviour of water-soluble organophosphine complexes of palladium (II) - Meij, Anna Magrietha Magdalena (University of the Free State, 2001)
The aim of this study was to prepare complexes of the type [PdCI(PT A)3]Cl and cis- [PdCh(PTA)2] (pTA = 1,3,5- triaza-7-phosphaadamantane) and to investigate i) the stability, ii) protonation behaviour, and iii) the substitution behaviour with halides/pseudo-halides, of these complexes in aqueous solution. Structure determinations were done by X-ray crystallography and two square planar complexes, trans-[Pd(SC~)2(pTA)2](SCN)2 and trans-[PdBr2(PTA)2] were reported. Both crystallize in the monoclinic space group, P21/n, refined to final R values of 2.88 % and 4.15 %, respectively. For the trans-[Pd(SCN)2(PTA)2](SCN)2 complex it was observed that both the PTA ligands are protonated at one of the N atoms, while two thiocyanate moieties acts as counterions and occupy the axial positions. Both the [PdCI(PT A)3t and cis-[PdCh(PT A)2] complexes hydrolyze and decompose when dissolved in water. However, in an excess of chloride hydrolysis is prevented to a large extent. In solution, a dynamic equilibrium exists between [PdCI(PT A)3r and cis- [PdCh(PT A)2] and over a period of time, depending on the chloride concentration added, [PdCI(PT A)3r slowly converts to cis-[PdCh(PT A)2]. In acidic medium [PdCI(PT A)3r rapidly converts to cis-[PdCh(PT A)2 and two pH dependences are observed; i.e., pKal = 5.11(4) and pKa2 = 2.92(6), which are assumed to represent the protonation of the [PdCI(PTA)3t and [PdCh(PTA)2] complexes respectively. The addition of a halide/pseudo-halide, Y, (Y = Br, I, SCN and N3) to [PdCI(PTA)3t in neutral solution (pH = 5.0-6.5), results in the rapid substitution of the chloride to form, as final product, trans-[PdY2(PT A)2]. Similarly, upon addition of a halide/pseudo-halide, Y, to cis-[PdCh(PT A)2], the trans product is formed. Larger equilibrium constants were obtained for cis-[PdCh(PTA)2] and Y (K24), than for [PdCI(PTA)3t and Y (K14) (K24 = 3.0(3)x103, 1.1(6)x102, 6.0(4)x10 and 4.1(3) Ml, for I', SCN, N3- and Br', respectively, and K14 = 5.8(4)x102, 1.9(4)x10 and 3.0(3) Ml, for r, SeN and Br", respectively). High reactivity of all the complexes investigated was observed and it was not possible to study these complexes by time-resolved spectroscopy. Significant line-broadening on 35Cl Nl\1R was observed which enabled the study of the rapid chloride exchange for [PdCl(PT A)3t. It was observed that the higher the concentration of the chloride, the smaller the rate of chloride exchange becomes. It is concluded that two species contributed to the exchange, the [PdCl(PT A)3t and a palladium-aqua species, probably [Pd(OH)2(PTA)3t The chloride exchange rate constant for the [PdCI(PTA)3f, at 22°C, was determined as 1.64(8)xl05 M-IS-I. Both the [PdCl(PT A)3t and cis-[PdCh(PT A)2 complexes showed complicated solution behaviour as indicated in the scheme included in the full text.

Die primêre doel van hierdie studie was die bereiding van komplekse van die tipe [PdCl(PT A)3]CI en cis-[PdCh(PTA)2] (PTA = 1,3,5-triaza-7-phosphaadamantaan), asook om die volgende eienskappe van hierdie komplekse in waterige oplossing te ondersoek: i) stabiliteit, ii) protoneringsgedrag, en iii) substitusiegedrag met haliede en pseudo-haliede. Struktuurbepalings is gedoen met behulp van X-straal kristallografie en twee vierkantig planêre komplekse, trans-[Pd(SCN)2(PTA)2](SCN)2 en trans-[PdBr2(PT A)2], is gerapporteer. Beide kristalliseer in die monokliniese ruimte groep, P21/n, en onderskeidelike R-waardes van 2.88% en 4.15% is verkry. Vir die trans-[Pd(SCN)2(PTA)2](SCN)2 kompleks is waargeneem dat beide die PTA ligande geprotoneer is byeen van die N atome, terwyl twee tiosianaatanione as teenione optree en die aksiale posisie beset. Beide die [PdCI(PT A)3t en cis-[PdCb(PT A)2] komplekse hidroliseer en ontbind wanneer dit opgelos word in waterige media. Hidrolise word egter tot 'n groot mate beperk indien 'n oormaat chloried teenwoordig is. 'n Dinamiese ewewig bestaan in oplossing tussen [PdCI(PTA)3t en cis- [PdCh(PTA)2] en afhangend van die chloriedkonsentrasie wat bygevoeg is, ontbind [PdCl(PT A)3t stadig om die cis-[PdCb(PT A)2] kompleks te vorm. In suurmedium ontbind [PdCI(PT A)3t vinnig om die cis-[PdCb(PTA)2] kompleks te vorm en twee pH afhanklikhede is waargeneem; nl., pKal = 5.11(4) en pKa2 = 2.92(6) en dit word aanvaar dat dit onderskeidelik die protonering van die [PdCI(PTA)3t en [Pd(Cl)2(PTA)2] komplekse, verteenwoordig. Die byvoeging van 'n halied/pseudo-halied, Y, (Y = Br, I, SCN and N3) by [PdCI(PT A)3t, in neutrale oplossing, (pH = 5.0-6.5), lei tot die vinnige substitusie van die chloried om trans- [PdY2(PTA)2] as finale produk te gee. Soortgelyk, met die byvoeging van 'n halied/pseudo-halied, Y, by cis-[PdCb(PTA)2] word die trans produk gevorm. Groter ewewigkonstantes is verkry vir cis-[PdCb(PTA)2] met Y (K24), as vir [PdCI(PTA)3t met Y (K14) (K24 = 3.0(3)x103, 1.1(6)x102, 6.0(4)x10 en 3.0(3) M-I vir I', SCN-, N3- en Br, onderskeidelik en K14 = 5.8(4)x102, 1.9(4)x10 en 3.0(3) M-I vir I, SCN en Br", onderskeidelik). Vir al die komplekse wat ondersoek is, is gevind dat dit hoogs reaktief is en dit was gevolglik nie moontlik om die komplekse met behulp van konvensionele metodes van spektroskopie (bv. stopvloei) te bestudeer nie. Betekenisvolle lynverbreding op 35Cl KMR is waargeneem wat die bestudering van vinnige chlorieduitruiling vir [PdCI(PT A)3f moontlik gemaak het. Daar is gevind dat hoe hoër die konsentrasie van die chloried, hoe kleiner die tempo van chlorieduitruiling word. Die gevolgtrekking kan gemaak word dat twee spesies bydraes maak tot die uitruiling, nl., die [PdCI(PTA)3t en die palladium-akwa spesie, waarskynlik [Pd(OH2)(PTA)3t. Die tempokonstante vir die chlorieduitruiling van die [PdCI(PTA)3t, by 22°C, is bereken as 1.64(8)x105 Mis-I. Beide die [PdCI(PT A)3t en cis-[PdCh(PTA)2] het komplekse oplossingsgedrag getoon, soos aangedui in die volgende skema ingesluit op die volledige teks
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2001
Keywords: Chemical reactions; Substitution reactions